2020
DOI: 10.4082/kjfm.18.0015
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking in South Korea: A Narrative Review

Abstract: Although the prevalence of cigarette smoking has declined in Western countries over the past few decades, a comparable decline among males has not been observed in Asian countries, especially in South Korea, where approximately 40%-50% of men and 4%-8% of women have been identified as smokers, and there is a pressing need to understand the background of cigarette smoking in these populations. The present study is a narrative review of the research literature on cigarette smoking in South Korea. First, we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 60 publications
5
60
1
Order By: Relevance
“…Four of these Asian countries (China, India, Indonesia and Japan) ranked in the top ten in smoking prevalence worldwide, while only two of the included Caucasian countries (USA and Germany) were ranked in the top ten 81,82 . Smoking is also a highly prevalent social habit in South Korea and Malaysia, 83,84 contributing to high active and passive smoking among Asians. Active smoking is a well‐known risk factor for the development of TED, and previous meta‐analysis has suggested four times higher odds of development of TED among smokers 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Four of these Asian countries (China, India, Indonesia and Japan) ranked in the top ten in smoking prevalence worldwide, while only two of the included Caucasian countries (USA and Germany) were ranked in the top ten 81,82 . Smoking is also a highly prevalent social habit in South Korea and Malaysia, 83,84 contributing to high active and passive smoking among Asians. Active smoking is a well‐known risk factor for the development of TED, and previous meta‐analysis has suggested four times higher odds of development of TED among smokers 5 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of smoking and COVID-19 by Simons, et al found that a similar underrepresentation was apparent in seven other countries: Italy, Israel, Kuwait, Mexico, Spain, Switzerland, and the U.K. 4 They found only marginal under-representation in South Korea and a reversed pattern in Iran. Using sex-adjusted rates of smoking prevalence there was moderate under-representation of smokers in South Korea --18.5% of 28 hospitalized patients 5 vs a sexadjusted national rate of 28.6%, 6 and in Iran --14% of 490 hospitalized COVID-19 patients 7 vs. a sex-adjusted national rate of 24.6%. 8 Additionally, a small study from Germany found a smoking rate of 6% of 50 hospitalized patients 9 vs. a sex adjusted national rate of 24.9%.…”
Section: Introductionmentioning
confidence: 93%
“…In 2018, the seventh Korea National Health and Nutrition Examination Survey (KNHANES) showed that the cigarette smoking prevalence was 36.7% among male adults and 7.5% among female adults. To reduce the smoking rate, the South Korean government has implemented various anti-smoking regulations such as raising cigarette prices and tax, expansion of smoke-free areas, and banning of tobacco advertisements in stores [4]. Following the recommendation of the WHO's Framework Convention of Tobacco Control, the Ministry of Health and Welfare of South Korea have modified and complemented GHWs on the cigarette packages over a period of time [5].…”
Section: Introductionmentioning
confidence: 99%